Multi-criteria approach for selecting the best solid waste management technologies - A.M. Latifah; Hassan Basri; Noor Ezlin Ahmad Basri (Universiti Kebangsaan Malaysia, 2010)
The growth in urbanization and industrial activities has caused solid waste management problems. As a solution the integrated approach has been chosen to manage the solid waste. Developing and implementing integrated solid waste management involve combined technologies and alternatives which are suitable with local laws condition. This research showed that Analytical Hierarchy Process (AHP) has the potential as a decision making tool that can be used in selecting process of solid waste management technology. Three levels hierarchy was developed with the goal at the top level, followed by criteria and alternatives. By using this technique, the priority of each considered technology will be determined where technology with the highest priority is more suitable to be developed. Sensitivity analysis was carried out to test the sensitivity of final decision towards inconsistency of judgement. Application of AHP to determine priority in selecting solid waste management technology was explained in this research based on a case study in the Port Dickson Municipal Council. Analysis of result showed that the combination of recycling technology and composting are suitable to be applied in the Port Dickson district.